Trends in diarrhoeal disease hospitalizations to a short stay paediatric ward at the Chris Hani Baragwanath hospital from 2002 to 2016 - Makgatho, Euphrasia (My University, 2019)
Globally, a decline in diarrhoeal disease has been observed over the last two decades. This may be attributable to several interventions, including rotavirus vaccination since 2009 in South Africa. From January 2002 to December 2016, we conducted a retrospective trend analysis of diarrhoeal hospitalisations with mild or moderate dehydration to a short stay ward (SSW) in children less than 14-years of age. We found that diarrhoeal hospitalisation to the SSW accounted for 29.3% of the 53 717 children that presented with diarrhoea to the emergency department. A significant decline in disease incidence was noted after 2009/ 2010, coinciding with rotavirus vaccine implementation into the Expanded Programme on Immunisation. The yearly incidence (per 100 000) declined from 307 (95%CI: 277- 337) over the 2002-2008 period to 141 (95%CI: 120- 161) from 2011-2016; p<0.001. In conclusion, we report a temporal association between rotavirus vaccination and diarrhoeal disease hospitalisations to the SSW at this hospital
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Masters of Medicine Johannesburg, 2019